If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 334 = w(w + 6) Reorder the terms: 334 = w(6 + w) 334 = (6 * w + w * w) 334 = (6w + w2) Solving 334 = 6w + w2 Solving for variable 'w'. Reorder the terms: 334 + -6w + -1w2 = 6w + -6w + w2 + -1w2 Combine like terms: 6w + -6w = 0 334 + -6w + -1w2 = 0 + w2 + -1w2 334 + -6w + -1w2 = w2 + -1w2 Combine like terms: w2 + -1w2 = 0 334 + -6w + -1w2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -334 + 6w + w2 = 0 Move the constant term to the right: Add '334' to each side of the equation. -334 + 6w + 334 + w2 = 0 + 334 Reorder the terms: -334 + 334 + 6w + w2 = 0 + 334 Combine like terms: -334 + 334 = 0 0 + 6w + w2 = 0 + 334 6w + w2 = 0 + 334 Combine like terms: 0 + 334 = 334 6w + w2 = 334 The w term is 6w. Take half its coefficient (3). Square it (9) and add it to both sides. Add '9' to each side of the equation. 6w + 9 + w2 = 334 + 9 Reorder the terms: 9 + 6w + w2 = 334 + 9 Combine like terms: 334 + 9 = 343 9 + 6w + w2 = 343 Factor a perfect square on the left side: (w + 3)(w + 3) = 343 Calculate the square root of the right side: 18.520259177 Break this problem into two subproblems by setting (w + 3) equal to 18.520259177 and -18.520259177.Subproblem 1
w + 3 = 18.520259177 Simplifying w + 3 = 18.520259177 Reorder the terms: 3 + w = 18.520259177 Solving 3 + w = 18.520259177 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + w = 18.520259177 + -3 Combine like terms: 3 + -3 = 0 0 + w = 18.520259177 + -3 w = 18.520259177 + -3 Combine like terms: 18.520259177 + -3 = 15.520259177 w = 15.520259177 Simplifying w = 15.520259177Subproblem 2
w + 3 = -18.520259177 Simplifying w + 3 = -18.520259177 Reorder the terms: 3 + w = -18.520259177 Solving 3 + w = -18.520259177 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + w = -18.520259177 + -3 Combine like terms: 3 + -3 = 0 0 + w = -18.520259177 + -3 w = -18.520259177 + -3 Combine like terms: -18.520259177 + -3 = -21.520259177 w = -21.520259177 Simplifying w = -21.520259177Solution
The solution to the problem is based on the solutions from the subproblems. w = {15.520259177, -21.520259177}
| [36]/3= | | -1-15=-3t+t | | 2g=g+5 | | [36]3= | | 6+2(3j-2)=4(1-j) | | 5x-10+3x=7+8x-17 | | x+x+2+x+4+x+6=188 | | -16t^2+484= | | 4x-x+6=3x-2+6 | | w^3-5w^2-14w=0 | | 6(4-2x)=3(4x+8) | | 12+2x=4x/4+2x | | 0=12.5x-4.9x^2 | | -(8y+3)-(-7y-7)=-2 | | -3p-4=2p | | a+3-4=-1 | | -5+13x=-6x^2 | | -9v=27 | | 48-(12)= | | 3(c-22)=2(c-6) | | r^2+2r-7=0 | | 3.7=.21w | | -12h+39=-4h-7 | | 12(4x-4)=4(12x+1) | | 40+15+0.25x=45+45+0.35x | | 8(x-6)+(-3x)=5(x-6)+3 | | 2h-35=2h+15 | | -8+4=5u-3u | | 4s-6=7s+3 | | (2x+1.5).15=11.5 | | 4.2+1.7x=2.7x | | 64n^2+36=0 |